Code-switching and cognitive control: a review of current trends and future directions - Özkara, Basak; Cedden, Gülay; von Stutterheim, Christiane; Meyer, Patric (Frontiers in Language Sciences, 2025)
Bilinguals frequently switch between their languages, a phenomenon known as code-switching (CS). CS is supposed to interact with cognitive control, making theories of cognitive control crucial for understanding bilinguals' CS behavior. This article reviews four prominent frameworks of cognitive control as they pertain to CS. We critically assess each framework and examine empirical studies that test their predictions. In doing so, we highlight the strengths and limitations of these models, ultimately discussing their compatibility. We conclude by proposing avenues for future research and suggesting potential pathways toward developing a comprehensive framework of cognitive control in CS.